Ideas : general introduction to pure phenomenology - Husserl, Edmund, 1859-1938 (Husserl, Edmund, 1859-1938. Ideen zu einer reinen Phänomenologie und phänomenologischen Philosophie., 2002)
First published in 2002. Routledge is an imprint of Taylor & Francis, an informa company.